Design of pore layout for perforated auxetic metamaterials with low-frequency band gaps. (25th March 2020) - Tian, Xiangyu; Chen, Wenjiong; Gao, Renjing; Liu, Shutian; Wang, Jiaxing
Abstract: We propose two types of perforation layout by introducing hole rotation based on regular configuration for effective band gap generation and mechanical properties improvement in low porosity. The design is characterized by redistribution of the substrate materials, and reduction connector thickness. Our analysis not only shows that the proposed layouts obtain broad and multiple band-gaps in low-frequency ranges and exhibit extreme Young's modulus variations, but also reveals how the reduction of connector thickness and geometric symmetry contribute to the unusual response. This study provides a perspective to design auxetic perforated metamaterials of low porosity with wide and low-frequency band gaps.